25 The surgical workload of adult congenital heart disease at the national cardiothoracic and transplant unit, Ireland: a 5 year review. (7th October 2015) - Daly, A; Cullen, P; McGuinness, J; Redmond, M; Nolke, L
Abstract : Introduction: The prevalence of Adult Congenital Heart Disease (ACHD) is increasing both in Ireland and worldwide. This is attributed to improved paediatric cardiology and cardiac surgery, with advances in detecting, monitoring and treating congenital heart disease. Many patients require future surgery, often in their adult lives. We aimed to evaluate the surgical workload of ACHD in Ireland. Methods: All patients with ACHD undergoing cardiac surgery in the National Centre for Cardiothoracic Surgery from January 2009 to December 2013 were identified from the Cardiac Surgery database and cross-referenced with theatre records (n = 138) (Figure 1 ). Review of patient charts and electronic patient records was performed. Data extracted included patient demographics, underlying diagnosis, previous interventions, surgery performed and its indications, as well as post-operative course and cardiac surgery follow up. Procedures were divided into simple and complex procedures for comparison. Results: 61% were male (n = 84). Mean age was 31.5 years, range 16–72 years. 53% (n = 74) had previous cardiac surgery (Figure 1 ). Valvular procedures were most commonly performed (46%) followed by septal surgeries (31%). Device implantation or change made up 5% of interventions. Median ICU stay was 1 day with a median time to discharge of 7 days. Median surgical follow up was 7 weeks (range 4 to 170 weeks) with a median of 1 outpatient review. Comparisons between those undergoing first-time surgery and re-operations were made, as well as between simple and complex procedures. Conclusion: ACHD patients comprise a small component of the total work done in any adult centre but this group requires an ongoing specialist interest.